Efeito dos hormônios tiroidianos no comportamento de camundongos 3xTg-AD (APPswe, PS1m146v, tauP301L) modelo da doença de Alzheimer - Maglione, Andrea Vancetto [UNIFESP] (2019)
Alzheimer disease’s (AD) is characterized by dementia, compromising cognitive and behavioral functions. It is known that the central nervous system is an important target of thyroid hormones (TH) and an inverse association between serum FT3 levels and the risk of developing AD has been reported. The aim of this study was to evaluate the effects of triiodothyronine (T3) treatment on the depression-like behavior observed in male transgenic 3xTg-AD (APPswe, PS1m146v, tauP301L) mice. The animals were divided into 2 groups. One group received daily intraperitoneal injections of 20 ng/g of L-T3 (T3 group), and the other group was administered an equivalent volume of 0.9% saline (Control group). The experimental protocol lasted 21 days, and behavioral tests were conducted on Days 15-21. At the conclusion of the experiment, the TH profile and hippocampal gene expression were evaluated in samples from T3-treated and control animals. It was observed that the T3-treated group presented significantly increased serum T3 and decreased thyroxine (T4) levels. When compared to control hippocampal samples, we also observed attenuated glycogen synthase kinase-3 (GSK3), metalloproteinase 10 (ADAM10), amyloid beta precursor -protein (APP), serotonin transporter (SERT), 5HT1a receptor, monocarboxylate transporter 8 (MCT8) and bone morphogenetic protein 7 (BMP-7) and augmented superoxide dismutase 2 (SOD2) and Hairless gene expression in the T3 group. T3-treated animals displayed reduced immobility times in both the tail suspension and forced swim tests, and in the latter also presented higher latency times, when compared to the control group. Taken together, our results demonstrate that in an AD mouse model, T3 supplementation promotes improvements in depression-like behavior acting through the modulation of the serotonergic pathway. The benefits of T3 therapy are not only restricted treating - related depression but is also involved in disease progression.